An impedimetric response study for the efficient detection of breast cancer specific biomarker CA 15-3 using a tin oxide thin film based immunoelectrode. Issue 46 (13th November 2017) - Arora, Kashima; Tomar, Monika; Gupta, Vinay
Abstract : A novel and sensitive RF magnetron sputtered tin oxide (SnO2 ) thin film based breast cancer immunosensor that combines exquisite sensitivity, rapid determination and specificity with a simple, inexpensive and easy-to-use technology has been realized. Abstract : A novel and sensitive RF magnetron sputtered tin oxide (SnO2 ) thin film based breast cancer immunosensor that combines exquisite sensitivity, rapid determination and specificity with a simple, inexpensive and easy-to-use technology has been realized. A SnO2 thin film based biocompatible matrix has been used for immobilization of breast cancer specific antibody CA 15-3 by a physical adsorption technique for an efficient detection of breast cancer antigen CA 15-3. The fabricated immunoelectrode (antibody CA 15-3 (Ab)/SnO2 /Pt/Ti/glass) has been characterized using scanning electron microscopy (SEM), cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The optimal equivalent circuit model that matches the impedimetric responses of the immunoelectrode describes three distinct regions: the electrolyte solution resistance ( R s ), the double layer capacitance ( C dl ) and the specific charge transfer resistance ( R ct ). The SnO2 thin film based immunosensor produces a decrease in the peak oxidation current in CV and DPV studies due to the steric hindrance caused by the macromolecular antibody. The immunoelectrode (Ab/SnO2 /Pt/Ti/glass) exhibits a linear increase in electrochemical impedance response upon combining with the specific antigen CA 15-3, in a wide range of antigen concentration from 50 ng dL −1 to 700 ng dL −1 (8 U mL −1 to 120 U mL −1 ) with a R ct sensitivity of 38.63 (ng dL −1 ) −1, fast response time and a high shelf life of more than 20 weeks.